Chondroprotective and anti-inflammatory effects of sesamin - Phitak T. (2014)
Osteoarthritis (OA) is a major disability of elderly people. Sesamin is the main compound in Sesamun indicum Linn., and it has an anti-inflammatory effect by specifically inhibiting Δ5-desaturase in polyunsaturated fatty acid biosynthesis. The chondroprotective effects of sesamin were thus studied in a porcine cartilage explant induced with interleukin-1beta (IL-1β) and in a papain-induced osteoarthritis rat model. With the porcine cartilage explant, IL-1β induced release of sulfated-glycosaminoglycan (s-GAG) and hydroxyproline release, and this induction was significantly inhibited by sesamin. This ability to inhibit these processes might be due to its ability to decrease expression of MMP-1, -3 and -13, which can degrade both PGs and type II collagen, both at the mRNA and protein levels. Interestingly, activation of MMP-3 might also be inhibited by sesamin. Moreover, in human articular chondrocytes (HACs), some pathways of IL-1β signal transduction were inhibited by sesamin: p38 and JNK. In the papain-induced OA rat model, sesamin treatment reversed the following pathological changes in OA cartilage: reduced disorganization of chondrocytes in cartilage, increased cartilage thickness, and decreased type II collagen and PGs loss. Sesamin alone might increase formation of type II collagen and PGs in the cartilage tissue of control rats. These results demonstrate that sesamin efficiently suppressed the pathological processes in an OA model. Thus, sesamin could be a potential therapeutic strategy for treatment of OA. © 2012 Elsevier Ltd. All rights reserved.